4(-5x-6)=-4

Simple and best practice solution for 4(-5x-6)=-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(-5x-6)=-4 equation:


Simplifying
4(-5x + -6) = -4

Reorder the terms:
4(-6 + -5x) = -4
(-6 * 4 + -5x * 4) = -4
(-24 + -20x) = -4

Solving
-24 + -20x = -4

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '24' to each side of the equation.
-24 + 24 + -20x = -4 + 24

Combine like terms: -24 + 24 = 0
0 + -20x = -4 + 24
-20x = -4 + 24

Combine like terms: -4 + 24 = 20
-20x = 20

Divide each side by '-20'.
x = -1

Simplifying
x = -1

See similar equations:

| x/5+17=20 | | 2(7-4x)=-74 | | 9y^2+27y+14= | | 7(-7x+8)=-483 | | 12x+23=71 | | x^3=167 | | 17.00+5.50h=11.00+6.75h | | 98=7x-7 | | 4y-5y=81 | | 10+4c=5(c-6)+33 | | 5+(-24)= | | 2.5d+7.75=4+3.25d | | 6(x+3)-4(x-3)= | | 3w^2(w^2+3)=8+7w^2 | | 13x+2=54 | | 835=5x^3 | | 360=106+84+y+38+3y+12 | | 5+7*5+5= | | 4x-8=4x+-36 | | 4d=9-d-8 | | 5+2*5+5= | | -2(-4+x)=20 | | 2x+2=6x-10 | | 6log(x)=9 | | m=15C+10 | | 29=8x-11 | | 166=4n | | 3(2x+6)+4x=38 | | 13+7=z | | 4x-3x+2x-3+5x= | | 10y+1.5y=7(1.5y)+y | | 3(2x+6)+4x=3 |

Equations solver categories